Herb-soil coupling in post-fire karst forests: a grey relational analysis in Yunnan, Southwest China - Zhang, Longhai; Zhang, Zhiyong; Li, Zihao; Chen, Xinjun; Pu, Shirui; Chen, Qian; Gong, Min; Khan, Muhammad Anas; Zhou, Jinxing (Frontiers in Plant Science, 2025)
Karst ecosystems, recognized as ecologically fragile systems, are characterized by vegetation-soil interaction mechanisms particularly vulnerable to wildfire disturbances. Understanding the post-fire coupling dynamics between vegetation and soil is crucial for guiding restoration in these vulnerable landscapes. This study investigated post-fire areas across five disturbance intensities (unburned, light, moderate, severe, extreme) in Jianshui County, Yunnan Province, China. We conducted a systematic analysis of soil physicochemical properties and herb diversity, and quantified the vegetation-soil coupling relationship using grey relational modeling. Key results reveal: (1) 21 herbaceous species were documented, with Asteraceae, Poaceae, and Fabaceae collectively constituting 76.2% of the flora. (2) Across the fire severity gradient, herbaceous diversity demonstrated an initial increase followed by a subsequent decline. (3) Grey correlation analysis identified soil pH, total potassium, and phosphatase activity as primary drivers of herb community variation. (4) Vegetation-soil coupling coordination followed a U-shaped trajectory, achieving optimal synergy (0.84, Higher coordination) under extreme-severity burns and minimal coordination (0.71, Medium coordination) in severe burns. These findings underscore that moderate fire regimes can play a positive role in enhancing the vegetation-soil coupling effect. Furthermore, the strategic regulation of soil pH and potassium availability during restoration emerges as a critical lever for optimizing ecosystem recovery and enhancing resilience. This study provides valuable insights for developing targeted post-fire management strategies in karst regions.